Partisan residential sorting on climate change risk - Bernstein, Asaf; Billings, Stephen B.; Gustafson, Matthew T.; Lewis, Ryan (Journal of Financial Economics, 2022)
Is climate change partisanship reflected in residential decisions? Comparing individual properties in the same zip code with similar elevation and proximity to the coast, houses exposed to sea level rise (SLR) are increasingly more likely to be owned by Republicans and less likely to be owned by Democrats. We find a partisan residency gap for even moderately SLR exposed properties of more than 5 percentage points, which has more than doubled over the past six years. Findings are unchanged controlling flexibly for other individual demographics and a variety of granular property characteristics, including the value of the home. Residential sorting manifests among owners regardless of occupancy, but not among renters, and is driven by long-run SLR exposure but not current flood risk. Anticipatory sorting on climate change suggests that households that are most likely to vote against climate friendly policies and least likely to adapt may ultimately bear the burden of climate change.